The Effect of Gender Equality on International Soccer Performance - Julia Bredtmann; Carsten J. Crede; Sebastian Otten (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
In this paper, we propose a new estimation strategy that uses the variation in success between the male and the female national soccer team within a country to identify the causal impact of gender equality on women's soccer performance. In particular, we analyze whether within-country variations in labor force participation rates and life expectancies between the genders, which serve as measures for the country's gender equality, are able to explain differences in the international success of male and female national soccer teams. Our results reveal that differences in male and female labor force participation rates and life expectancies are able to explain the international soccer performance of female teams, but not that of male teams, suggesting that gender equality is an important driver of female sport success.
Keywords: J16; L83; Z13; 330; international sport success; soccer; gender equality; fixed-effects estimation